Continuity and Transformation following the 1973 Coup d’état in Chile: Case Studies from the University of Chile Pedagogical Institute and the History Major Curriculum - Guzmán, Patricio (2026)
The article looks at the structural changes at the Pedagogical Institute (IP) of the University of Chile (UCh) during Chile’s civil-military dictatorship (1973-1990), focusing on the relationship between state intervention in education and the rigid institutional guidelines established after the collapse of the Popular Unity government. Using a qualitative approach and a historical–documentary design, the study examines the History degree programs from 1962 and 1975. Content analysis served as a tool of hermeneutic synthesis and triangulation to help interpret the material and connect it with the structural reforms that affected the History program and how its study plans were organized. Following the 1973 coup d'état, the University of Chile endured a critical period characterized by temporary closures, dismissals, waivers, campus persecution, and the hiring of unqualified people. These measures significantly impacted initial teacher education (ITE). The separation of the IP from the UCh in 1981 marked a major turning point in teacher education, establishing a technical–functional model that prioritized History as a discipline over critical pedagogy. History programs reflected this shift by simplifying its content and refraining from complex regarding historical events. Such modifications were, therefore, driven by factors beyond education—primarily related to political considerations or other external influences rather than effective teaching. This orthodox pragmatism, present in both the 1962 and 1975 programs, advocated for a positivist and linear approach to future teacher development, emphasizing the role of historians rather than holistic educators. According to the study, these enhancements which impacted pedagogical training, were influenced by the prevailing political climate of the period marked by repression and government control. The essay provides guidelines for further research to examine the connection between educational developments and the political landscape as a framework for reflection on continuity and change during the initial stages of teacher training programs.